2023
DOI: 10.1186/s13287-023-03368-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem/stromal cells-derived extracellular vesicles as a potentially more beneficial therapeutic strategy than MSC-based treatment in a mild metabolic osteoarthritis model

Abstract: Background Mesenchymal stromal/stem cells (MSCs) and MSC-derived extracellular vesicles (MSC-EVs) hold promise as a disease modifying treatment in osteoarthritis (OA). Obesity, and its associated inflammation, contribute to OA development and metabolic OA represents a specific and significant group of the OA patient population. Given their immunomodulatory properties, MSC and MSC-EVs are especially interesting for this group of patients as a therapeutic option. Here, we were the first to compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…The left knee joints of all animals were preserved (no surgical intervention) and served as a non-surgery control. Although it is well-documented that OA in one knee joint can lead to abnormal biomechanics in other joints in humans and dogs, and in DMM mouse models ( Mundermann et al, 2005 ; Bockstahler et al, 2009 ; Metcalfe et al, 2013 ; Fouasson-Chailloux et al, 2021 ; Alves et al, 2022 ), our relatively mild OA model with unilateral groove surgery did not show significant differences in weight bearing between the left and right joints when untreated, as shown previously ( Warmink et al, 2023 ). All surgeries were performed under general anesthesia (isoflurane–induced at 4%, maintained at 2.5%), and analgesia (0.01 mg/kg buprenorphine, injected subcutaneously prior to surgery, and 6–8 h after first injection).…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The left knee joints of all animals were preserved (no surgical intervention) and served as a non-surgery control. Although it is well-documented that OA in one knee joint can lead to abnormal biomechanics in other joints in humans and dogs, and in DMM mouse models ( Mundermann et al, 2005 ; Bockstahler et al, 2009 ; Metcalfe et al, 2013 ; Fouasson-Chailloux et al, 2021 ; Alves et al, 2022 ), our relatively mild OA model with unilateral groove surgery did not show significant differences in weight bearing between the left and right joints when untreated, as shown previously ( Warmink et al, 2023 ). All surgeries were performed under general anesthesia (isoflurane–induced at 4%, maintained at 2.5%), and analgesia (0.01 mg/kg buprenorphine, injected subcutaneously prior to surgery, and 6–8 h after first injection).…”
Section: Methodssupporting
confidence: 81%
“…We considered a difference between means of 3 points in the primary outcome (total OARSI score) clinically relevant, with a corrected α = 0.01, β = 0.2, and aiming for a power of 80%. Based on previous research the variance in grooved animals was estimated at σ 2 = 1.21 and in ungrooved animals σ 2 = 0.56 ( de Visser et al, 2017 ; de Visser et al, 2018a ; de Visser et al, 2019 ; Warmink et al, 2022 ; Warmink et al, 2023 ). This resulted in 4 animals in the grooved groups and 3 animals in the ungrooved groups, thus a total of 7 animals per diet group would be sufficient.…”
Section: Methodsmentioning
confidence: 99%
“…MSC-EVs are able to promote a greater resolving phenotype than the parent cells in a model of murine OA [13]. In fact, in a metabolically induced model of rat OA, MSC infusion further exacerbated cartilage degradation whereas MSC-EVs did not [14].…”
Section: Introductionmentioning
confidence: 96%
“…Compared with cell therapy, EVs have several advantages; for example, non-immunogenicity, non-infusion toxicity, relatively higher stability in the blood circulation, easier access, uncomplicated preservation, and ethical issues (12). For clinical application, MSC-EVs attenuate patients suffering from steroid refractory graft-versus-host disease, ostheoarthitis, and grade III-IV chronic kidney disease (13)(14)(15). In sepsis, pre-clinical studies in animal models have demonstrated the bene cial e cacy of MSC-EVs in sepsis; however, the impacts of MSC-EV treatment are still inconclusive.…”
Section: Introductionmentioning
confidence: 99%